Marketing low cost airline services to business travellers. - Mason, Keith J. (Elsevier, 2001)
A number of EU low-cost airlines have reported their success in attracting business travellers on some of their routes. Recent research shows that business travellers working for small companies are more willing to trade in-flight service, frequency and FFP points for lower fares than those working for larger companies. A survey of short haul business travellers using a major carrier at Heathrow airport is compared with travellers of a low-cost airline at a secondary London airport. The hypothesis that business travellers using low-cost airlines form a separate market segment from business travellers using full-service airlines is not shown. Short haul business travellers are, en masse, becoming increasingly price sensitive. Travellers using network carriers use low-cost airlines and vice versa. Corporate influence in purchase decision making is more evident in travellers choosing network carriers and this is partly a function of the size of the company, with larger companies favouring such carriers. Marketing implications for both low-cost and full-service airlines are discussed.
Keywords: Low-cost airlines; Business travellers; Marketing